The effect of SGLT-2 inhibitors on cardiorespiratory fitness capacity: A systematic review and meta-analysis - Peng, Yong; Qin, Di; Wang, Yudi; Xue, Lian; Qin, YaXuan; Xu, Xin (Frontiers in Physiology, 2023)
Abstract Objective: To evaluate the effect of SGLT-2 inhibitors on various parameters of exercise capacity, and to provide evidence-based basis to T2DM combined with heart failure (HF) patients or HF patients without T2DM who apply SGLT-2 inhibitors to improve cardiorespiratory fitness. Methods: According to PICO (participant, intervention, comparison, outcome) elements, the effects of SGLT-2 inhibitors administration on VO2 or VO2peak were researched in the study. Weighted mean difference (WMD) and 95% confidence intervals (CIs) were calculated (random-effects model), Heterogeneity is assessed by I2 test. Results: Six studies were included according to the eligibility criteria, four of which were RCTs and another two were Non-RCTs. Compared with the control group, the merge results of RCTs showed that SGLT-2 inhibitors could increase the VO2peak (WMD,2.02 mLKg-1min-1, 95%CI: 0.68-3.37, p=0.03; I2 =0%, P =0.40) and VAT (WMD, 1.57 mLKg-1min-1, 95%CI: 0.06-3.07, p=0.04; I2 =0%, P =0.52) significantly of the obesity population, patients with T2DM and chronic HF patients with or without T2DM. Subgroup analysis showed that SGLT-2 inhibitors improve the VO2peak in non-HF patients (WMD,3.57 mLKg-1min-1, 95%CI: 0.87-6.26, p=0.009; I2 =4%, P =0.31) more than HF patients(WMD,1.46 mLKg-1min-1, 95%CI: -0.13-3.04, p=0.07; I2 =0%, P =0.81).Moreover, the merge of single arm studies also indicated that Empagliflozin could improve VO2peak (MD, 1.11 mLKg-1min-1, 95%CI: 0.93-1.30, p=0.000; P =0.827; I2 =0%) of T2DM patients with chronic HF. Conclusion: Despite the limitation number of studies and samples involved, the meta-analysis preliminarily demonstrated that SGLT2 inhibitors could improve some parameters of exercise capacity (VO2peak, VAT) in chronic HF patients with or without T2DM and obesity people, which had positive effect on promoting cardiopulmonary fitness to help these populations improve prognosis.